(untitled) (International Journal of Innovative Technologies in Economy, 2024)
Algerian policy for economic development has taken the agricultural sector as pillars, which is not without risk because of the vulnerability of the sector (climate change, the immensity of desert areas, etc.) but also because of the faillur of the various policies initiated until today. The challenge are high, and the benefits that can emerge are capable of guaranteeing sustainable development for the country. The current research aims to determine the impact of Agricultural and rural renewal in province of Constantine. Constantine is a proven agricultural center in eastern Algeria; the province has experienced agricultural dynamics since the beginning of the 2000s, which has resulted in increases in surface areas and yields. This increase did not have as a corollary an increase in production, which remains quite low compared to national efforts and ambitions; This analysis reveals that the main causes remain the low use of irrigation and the impact of climate change on annual rainfall.